2021
DOI: 10.3389/fonc.2020.603864
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three Autophagy-Related Long Non-Coding RNAs as a Novel Head and Neck Squamous Cell Carcinoma Prognostic Signature

Abstract: Head and neck squamous cell carcinoma (HNSCC) has a poor prognosis. Considerable evidence indicates that autophagy and non-coding RNA play essential roles in the biological processes involved in cancers, but associations between autophagy-related long non-coding RNAs (lncRNAs) and HNSCC remain unclear. In the present study, HNSCC RNA sequences and autophagy-related gene data were extracted from The Cancer Genome Atlas database and the Human Autophagy Database. A total of 1,153 autophagy-related lncRNAs were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…EMT is a process in which epithelial cells acquire mesenchymal cell characteristics and is closely related to tumor invasion, metastasis, and chemotherapy resistance in tumor progression ( Lamouille et al, 2014 ; Pastushenko and Blanpain, 2019 ; Xing et al, 2019 ; Guo et al, 2020 ). The molecular mechanisms involved in the transition from an epithelial phenotype to a mesenchymal state are complex and controlled by multiple signaling pathways ( Gugnoni and Ciarrocchi, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT is a process in which epithelial cells acquire mesenchymal cell characteristics and is closely related to tumor invasion, metastasis, and chemotherapy resistance in tumor progression ( Lamouille et al, 2014 ; Pastushenko and Blanpain, 2019 ; Xing et al, 2019 ; Guo et al, 2020 ). The molecular mechanisms involved in the transition from an epithelial phenotype to a mesenchymal state are complex and controlled by multiple signaling pathways ( Gugnoni and Ciarrocchi, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are defined as transcripts of more than 200 nucleotides that are not translated into proteins ( Xing et al, 2019 ; Guo et al, 2020 ). LncRNAs are crucial for cellular processes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed that lncRNAs exerts key roles in cancer progression [19], and dysregulated lncRNAs were involved with the incidence of HPV-related diseases [20][21][22]. It was reported up-regulation of lncRNA FEZF1-AS1 facilitates cervical carcinoma via sponging miR-367-3p [23].…”
Section: Discussionmentioning
confidence: 99%
“…The 5year survival rate of patients with HNSCC is less than 50% [6], which is attributed to lack of reliable prognostic biomarkers [25]. Recent studies have established a correlation between molecular markers such as autophagy genes, immune genes, autophagy-associated long noncoding RNAs (lncRNAs), and immune-related lncRNAs, and HNSCC prognosis [26][27][28][29], which may aid in determining clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%